Hydridoboranes as modifiers for single-site organochromium catalysts: from low- to ultrahigh-molecular-weight polyethylene - Mark, Stefan; Kurek, Alexander; Mülhaupt, Rolf; Xu, Rong; Klatt, Günter; Köppel, Horst; Enders, Markus (Angewandte Chemie. International edition, 2010)
Going to great lengths: The use of hydridoboranes as new modifiers for chromium-catalyzed olefin polymerization allows the preparation of polyethylene with a precisely tunable ultrahigh molecular weight. This effect can be understood by a reversible protection of the active catalyst by the borane (see scheme).